TENCON 2006 - 2006 IEEE Region 10 Conference 2006
DOI: 10.1109/tencon.2006.344141
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the IEEE 802.16 MAC Protocol with Varying Request Backoff Start

Abstract: A reservation based Medium Access Control (MAC) protocol has been adopted by the IEEE 802.16 standard as the basic protocol for data communication within the upstream channel. This standard adopts the binary exponential backoff algorithm with adjustable window size to resolve the collisions of request packets. This paper investigates the uplink access performance in terms of average throughput, average delay and collision probability for fixed number of contention slots, data slots and MAP size. The performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Then, we analyze the collision probability, access delay and network throughput for the analytical model. (17) In WiMAX's TBEB, a request will be dropped when the total number of retransmission times exceeds the specified threshold. However, IEEE 802.16 uses the same retransmission limit for different priorities nodes.…”
Section: Markov Chain Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, we analyze the collision probability, access delay and network throughput for the analytical model. (17) In WiMAX's TBEB, a request will be dropped when the total number of retransmission times exceeds the specified threshold. However, IEEE 802.16 uses the same retransmission limit for different priorities nodes.…”
Section: Markov Chain Analysesmentioning
confidence: 99%
“…(13)-(14) and the parameter r , the probability of state ( ,, ik-the closed-form feature of the Markov chain model, the sum of all states' probabilities is equal to one, as indicated in Eq (17)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies found in the literature focus on system performance regarding support of Quality of Service (QoS) [4][5][6][7] and cross-layer issues [8][9][10] for the IEEE 802.16 MAC protocol. However, only relatively few studies [11][12][13] explicitly approach the analysis of the Best Effort (BE) service class in comparison to other service classes (UGS, rtPS and nrtPS).…”
Section: Introductionmentioning
confidence: 99%